(untitled) (Annals of Bangladesh Agriculture, 2023)
A study was conducted in albida (Acacia albida) based agroforestry research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU) from November/2020-March/2021 to evaluate the performance of sunflower at different light intensity created by pruning off the albida canopy at different levels. The experiment was set up in a single-factor Randomized Complete Block Design with three replications. Five different treatments of the experiment were as follows; T1: albida tree (no pruning) T2: albida tree (25% pruning), T3: albida (50% pruning, T4: albida (75% pruning) and T5: sunflower sole cropping in open field. The results revealed that T1 treatment produced the tallest plant (100.72cm) followed by T2 (97.48cm) while the treatment T5 produced the shortest (72.95cm) plant. The fresh weight (81.67g) and dried weight (13.95g) of sunflower leaves were found maximum in T4 and the minimum fresh weight (53.48g) and dry weight (8.34g) were recorded in T1 treatment. The highest CGR (1.169mg/cm2/day) and RGR 66.58 (mg/g/day) values were found in T5 and was not significant with T4. The yield parameters of sunflower such as head diameter (15cm) and 1000 seeds weight (43.34g) were found maximum in T5 (open field) which was statistically similar to that of T4 treatment. The T5 yielded the highest (1.13t/ha) sunflower seeds followed by T4 (1.09t/ha). The study indicated that sunflower can be grown successfully under the albida tree canopy with 75% trimming. Ann. Bangladesh Agric. 27(2): 119-128